2018
DOI: 10.1190/geo2017-0190.1
|View full text |Cite
|
Sign up to set email alerts
|

3D numerical modeling of induced-polarization electromagnetic response based on the finite-difference time-domain method

Abstract: Induced-polarization (IP) effects have a significant influence on transient electromagnetic (TEM) data, which commonly manifest a reversed sign. Polarization media usually have a very high economic value. To study the IP effects, a new method for modeling the time-domain electromagnetic signals of 3D dispersive materials is developed. Due to the fractional time derivatives, two main difficulties are needed to be conquered: the derivation of Cole-Cole model impulse response function and the discrete recursion o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 24 publications
(6 citation statements)
references
References 73 publications
0
6
0
Order By: Relevance
“…The region containing the chargeable body is discretized with 10 ×10 ×10m uniform grids. The decay curve calculated by our SOE-BEDS algorithm and by [28] are shown in Figure 6, and the two decay curves agree well. The sign reversal caused by the IP effect can be clearly seen in both curves.…”
Section: B Accuracy Verificationmentioning
confidence: 58%
See 1 more Smart Citation
“…The region containing the chargeable body is discretized with 10 ×10 ×10m uniform grids. The decay curve calculated by our SOE-BEDS algorithm and by [28] are shown in Figure 6, and the two decay curves agree well. The sign reversal caused by the IP effect can be clearly seen in both curves.…”
Section: B Accuracy Verificationmentioning
confidence: 58%
“…Cai et al [27] developed a method to select the center point and orders for Padé series expansion adaptively during the time-stepping process, which improve the applicability of the algorithm. Ji et al [28] used a frequency-domain rational approximation method and the linear programming technique to convert the fractional order system into an integer order one. However, the limitation is that the coefficients and relaxation times of approximation functions depend on CCM exponent.…”
mentioning
confidence: 99%
“…Actually, from the analysis of the decay curves, we know that the slopes and sign reversals are the crucial IP characteristics. Thus, apart from the characteristic parameters about sign reversals such as time of sign reversal, the maximum absolute value of negative responses [7], [10], and the duration of negative values, we also need to pay attention to the slopes of curves.…”
Section: A Impact Degree Of the Ip Effects On Em Datamentioning
confidence: 99%
“…An overall analysis reported the influences of the polarization parameters, size, and buried depth of the target on the negative responses. They also demonstrated that only moderately sized, highly-polarizable media in a shallow layer could generally be detected [10].…”
Section: Introductionmentioning
confidence: 99%
“…For the past few years, the SIP forward and inversion method, taking the frequency domain Maxwell equation and Cole-Cole model as basis, or to say, taking both electromagnetic effect and IP effect into account, has deepened the research and understanding on the electromagnetic effect by leaps and bounds [2][3][4]. Nevertheless, difficulties still exist in both theoretical study and practical application, of which the electromagnetic effect and 3D inversion are of the greatest concern [5][6][7].…”
Section: Introductionmentioning
confidence: 99%